Exploring Possible Temporal Relationships of Unemployment and Crime: A Comment on Hale and Sabbagh - Cantor, David I. (Journal of research in crime and delinquency, 1991)
The article discusses the research carried out by the authors to show the relationship between unemployment and crime with reference to an article written by C. Hale and D. Sabbagh. According to Hale and Sabbagh, the time series consisting of levels of the variables are nonstationary and those consisting of the first differences are stationary. The substantive characteristics of the unemployment rate series imply that it cannot be represented as a simple series, such as a random walk with or without drift for an extended period of time, for if the series is taken to be a random walk with drift, both its mean and variance will increase linearly with time, even if the drift is set to zero, the variance of the series still increases linearly with time to infinity. The positive first-differenced unemployment rate effect appears either directly or indirectly through a structural specification of linkages mediated by other variables. Hale and Sabbagh also point out that the unemployment rate is not necessarily the best indicator of the business cycle. As recognized by Hale and Sabbagh, the U-C relationship is of interest because of its high profile to policymaker